2020
DOI: 10.1039/d0gc02247k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable synthesis of cyclodextrin-based polymers by exploiting natural deep eutectic solvents

Abstract: Natural deep eutectic solvents (NADES) represent an environmentally-friendly replacement of petroleum-based solvents, for this reason, they are a major field of research which aims to reduce the industrial emissions, looking...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Significant advances on the synthesis of CD-NSs [39], and their applications ranging from the environment [40] to other fields such as pharmacy, chemistry, agriculture, gene delivery, biomedicine and biotechnology, food, cosmetics, biocatalysis, etc., [6][7][8][9][10]22] have emerged over years. As judged from the historical development of CD-NSs [39], they have been the subject of numerous surveys, heading towards greener processes such as the CD-NSs synthesis in natural deep eutectic solvents (NADES) [41] and solvent-free CD-NSs synthesis [42]. Studies performed on the polymeric structure of ester-bridged βCD-NSs based on PMDA [27,[43][44][45] showed that the crosslinking degree is strongly dependent on the PMDA:β-CD molar ratio used during the CD-NSs synthesis, related to the swelling capacity as an important parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances on the synthesis of CD-NSs [39], and their applications ranging from the environment [40] to other fields such as pharmacy, chemistry, agriculture, gene delivery, biomedicine and biotechnology, food, cosmetics, biocatalysis, etc., [6][7][8][9][10]22] have emerged over years. As judged from the historical development of CD-NSs [39], they have been the subject of numerous surveys, heading towards greener processes such as the CD-NSs synthesis in natural deep eutectic solvents (NADES) [41] and solvent-free CD-NSs synthesis [42]. Studies performed on the polymeric structure of ester-bridged βCD-NSs based on PMDA [27,[43][44][45] showed that the crosslinking degree is strongly dependent on the PMDA:β-CD molar ratio used during the CD-NSs synthesis, related to the swelling capacity as an important parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The peak at around 3287–3306 cm −1 , which corresponds to hydroxyl groups, is present in all spectra [ 30 , 31 ]. The peak at 2894 cm −1 corresponds to the aliphatic C–H vibration in cellulose [ 33 , 34 , 35 , 36 ]. The peaks observed at around 1368 cm −1 and 1064 cm −1 are attributed to C–O and C–H groups present in the cellulose polysaccharide ring and C–O–C in the pyranose ring, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, either a sol-gel process or a precipitation polymerization can be observed, leading to the formation of a monolithic block or a precipitate, respectively. Also, in those cases in which the cross-linker is in the liquid form, and able to solubilize the CD, a melt polymerization can be performed [36,37].…”
Section: General Synthesis Protocolmentioning
confidence: 99%
“…Once the synthesis is completed, the solvent, the catalyst, eventual unreacted monomers, and by-products are removed from the synthesized product by purification with water or other volatile solvents. In the end, a dry solid powder is collected [37][38][39]. Another well-known approach to synthesize CD-NSs is achieved through simple dehydration reactions.…”
Section: General Synthesis Protocolmentioning
confidence: 99%